Heterozygous COL4A3/COL4A4 variants: diagnostic trends and clinical kidney outcomes - Yu Tanaka; Tomoko Horinouchi; Shuhei Aoyama; Yuka Kimura; Yuta Inoki; Yuta Ichikawa; Chika Ueda; Hideaki Kitakado; Atsushi Kondo; Nana Sakakibara; China Nagano; Tomohiko Yamamura; et al. (Clinical Kidney Journal, 2026)
Abstract Background Heterozygous pathogenic variants in COL4A3 or COL4A4 are relatively common and associated with a broad clinical spectrum. However, nomenclature and risk stratification remain unsettled. We aimed to investigate temporal diagnostic trends and clinical features of haematuria-positive individuals with heterozygous COL4A3/COL4A4 variants in a genetic testing cohort. Methods This retrospective cohort study involved 992 families genetically diagnosed with Alport syndrome at a single centre in Japan between 2006 and 2023. We identified 265 families comprising 299 haematuria-positive individuals with heterozygous pathogenic or likely pathogenic COL4A3/COL4A4 variants. For kidney failure (KF) analysis, 627 individuals, including affected relatives, were evaluated. Results At the family level, the proportion of the study group increased from 8.4% of genetically diagnosed Alport syndrome cases during the Sanger sequencing era (2006–2015) to 26.6% during early next-generation sequencing implementation (2015–2019), and 39.1% in the recent period (2020–2023). At genetic diagnosis, 75.3% of individuals had proteinuria and 4.7% had KF. Kaplan–Meier analysis showed that the median ages at first detection of haematuria and proteinuria, and at onset of KF, were 10, 26, and 72 years, respectively. Conclusions Individuals with haematuria and heterozygous COL4A3/COL4A4 variants accounted for an increasing proportion of genetically diagnosed cases of Alport syndrome. Although this referred cohort does not represent all individuals with heterozygous COL4A3/COL4A4 variants, our findings delineate the natural history of haematuria-positive individuals with these variants and may support early diagnosis and risk stratification aimed at preventing progression to KF.